Implementation of the Unified Theory of Acceptance and Use of Technology (UTAUT) 3 on the Sharia Bank Customer Behavior in Using Mobile Banking - Daulay, Nurfia Sintia; Rasyid, Arbanur; Cahyani, Utari Evy; Lubis, Rizki Mulia (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
Mobile banking has transformed banking services, yet the adoption of Islamic mobile banking in North Padang Lawas Regency remains low. This study examines the impact of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and personal innovation on behavioral intention and user behavior. Using a quantitative approach, 200 respondents were selected through random sampling, and data were analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS) via WarpPLS 7.0. Results show that performance expectancy (β = 0.508, p < 0.001), price value (β = 0.200, p = 0.002), habit (β = 0.248, p < 0.001), and personal innovation (β = 0.152, p = 0.014) significantly influence behavioral intention, while effort expectancy, social influence, facilitating conditions, and hedonic motivation do not. Behavioral intention (β = 0.293, p < 0.001) positively impacts user behavior, with facilitating conditions (β = 0.234, p < 0.001) and habit (β = 0.136, p = 0.024) also contributing, but personal innovation showing no effect. Additionally, behavioral intention does not mediate the influence of facilitating conditions, habit, or personal innovation on user behavior. These findings highlight the importance of emphasizing perceived usefulness, affordability, and habitual engagement to boost Islamic mobile banking adoption in the region.